ANALYSIS OF THE USE OF THE CODE OF ETHICS OF AGRICULTURAL ACCOUNTANTS USING QUANTITATIVE METHODS - Milojević, Ivan; Vladisavljević, Vladan; Tasić, Svetlana; Miljković, Miloš (Economics of Agriculture, 2023)
This paper investigates the possibility of applying the meta theory of strategic games in the domain of the ethical code of conduct of agribusiness accountants. The focus is on the case when an accountant detected incorrect financial reporting by the client’s management of material nature. As a generally quantitative method, the model of strategic games in such a case allows to quantify and find a balanced relationship between the interests of management and accountants in the world where, there is constantly sustainable problem of ethics and unethics of accountants, which is an extremely important issue in the agricultural sector, which is a developing branch.